2009
DOI: 10.1287/mksc.1080.0447
|View full text |Cite
|
Sign up to set email alerts
|

Findings—Retailer Promotion Pass-Through: A Measure, Its Magnitude, and Its Determinants

Abstract: We use data on all manufacturer funding and all promotion activity by a major US retailer during a two-year period to compute promotion pass-through and assess its magnitude. Then we estimate a two-tiered probit and lognormal regression model to study drivers of the large variation we observe in pass-through rates. Although our analysis is based on data from a single retailer, it provides a much more complete picture of the magnitude and variability of pass-through than has been available to date. Some key ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…The two features aggregate together to yield lower overall pass-though for private label SKUs (bottom panel of Figure 6). This finding is interesting in light of prior work which has found that retailers are more likely to pass through price promotions for private label products (Ailawadi and Harlam 2009). Together, these results suggest that the retailer is quite sensitive to the price of private label products.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…The two features aggregate together to yield lower overall pass-though for private label SKUs (bottom panel of Figure 6). This finding is interesting in light of prior work which has found that retailers are more likely to pass through price promotions for private label products (Ailawadi and Harlam 2009). Together, these results suggest that the retailer is quite sensitive to the price of private label products.…”
mentioning
confidence: 58%
“…The aggregate data approach to estimating pass-through was employed by Ailawadi and Harlam (2009) who examined the annual pass-through of trade promotion dollars. In particular, they calculated the annual total dollars spent by the manufacturer in the form of trade promotions and divided this by the annual dollars spent by the retailer in the form Author: Decision Stages and Asymmetries in Regular Retail Price Pass-through Article submitted to Marketing Science; manuscript no.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…whether the promotion applies to private label or manufacturer brands. Apart from margin differences (Ailawadi et al 2006) and differences in retailer pass-through (Ailawadi and Harlam 2009), these brand types may differ in their promotional appeal in small versus large outlets (Gijsbrechts et al 2003). Therefore, investigating the deal effectiveness of national brands and private labels across stores of varying selling areas may be a relevant topic for future study.…”
Section: Limitations and Future Researchmentioning
confidence: 99%